The Role of Generation Z in the Track Record of Time and Historical Transformation in the Lampung Metro City - Mukholidah, Nahrul; Wardani, Wardani (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2024)
Generation Z determines the management of local history and its preservation. However, Generation Z has no great determination in their involvement in preserving historical heritage. Therefore, this research focoses on completing how and what the role of generation z is in the track of time and history and historical transformation in Metro City. So that it can be their concern, about the struggle of heroes and colonization to advance and becom the forerunner City of Metro to proggres. The method used in this research is the historical method. Wich uses cultural heritage buildings, historical object and books, articles and other sources that can support the validity of the date. The result of the study indicate that generation z is the spearhead and leading actor to   maximize its role in recording the time and historical transformations that exist in City of Metro, including cultural heritage buildings and significant changes that occur in other historical relics as a forum for realizing the continuty of local historical cultural heritage in the City of Metro, Lampung.